Do SOX 404 Control Audits and Management Assessments Improve Overall Internal Control System Quality? - Schroeder, Joseph H.; Shepardson, Marcy L. (The Accounting Review, 2016)
ABSTRACT We address whether SOX 404(b) internal control audits under two auditing standards regimes and SOX 404(a) management assessments are associated with improved internal control system quality, an important and largely unstudied potential benefit. In 2013, the PCAOB disclosed that 15 percent of inspected control audits were ineffective, suggesting that the current control auditing standard may not be sufficient to induce implementation of high-quality control systems. We use an indirect measure of internal control system quality—future unaudited accruals quality—to proxy for internal control quality because sustained internal control improvements should be exhibited in future quarterly financial reports unaltered by contemporaneous financial statement audits. We find that internal control audits initially provided internal control quality benefits. After the 2007 auditing standards change, internal control quality deteriorated for ICFR audited versus unaudited firms. Finally, we find limited evidence that management assessments affect internal control quality. Results indicate that recent PCAOB concerns may have merit. Data Availability: Data are publicly available from the sources identified in the text.